Water conservation and water demand management pilot project: the case of Newcastle Municipality - Dube, Sandile Bonga (My University, 2017)
The Newcastle Local Municipality (NLM) has been experiencing water supply interruptions since 2010 due to high demand. Between June 2011 to December 2011, water losses ranged from 49% to 62% (about 23 to 30 megalitres per day) in Madadeni and Osizweni townships (Newcastle East). The suburban areas (i.e. Newcastle West) also experienced water interruptions due to collapsing and/or aging infrastructure. About a thousand households in Madadeni were involved in this study to find the cause of the high water losses. Awareness campaigns, repairing household leaks, installation of intelligent meters and the increase of free basic water in indigent households from 6kℓ to 12kℓ per month reduced water losses from about 246 kℓ to 177kℓ per month. If similar Water Conservation (WC) and Water Demand Management (WDM) could be rolled out to the 35 000 households in the NLM and similar results to those in Madadeni are attained, conservative water saving of about 21Mℓ per day could be achieved. This would reduce the demand on the Ngagane Water Treatment Works (WTW) by 20%.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2016
Keywords: Water-supply--South Africa--Management; Municipal water supply--South Africa; Water-supply--South Africa; Water conservation--South Africa--Management; Municipal water supply--Management